Fishery resource monitoring of the East China Sea via environmental DNA approach: a case study using black sea bream (Acanthopagrus schlegelii) - Zhang, Haobo; Zhou, Yongdong; Zhang, Hongliang; Gao, Tianxiang; Wang, Xiaoyan (Frontiers in Marine Science, 2022)
Understanding fish stock distribution is crucial in the context of sustainable fishery development. Traditional approaches such as net catching, mark recapturing and visual counting are often time consuming, less effective and prone to subjective bias. Recently, environmental DNA (eDNA) technology has made up for the shortcomings of traditional fishery resource survey methods and has been widely used for species monitoring, biodiversity assessment and biomass estimation. The eDNA method was used to analyse the distribution and biomass of the black sea bream (Acanthopagrus schlegelii) in the East China Sea. The black sea bream-specific primers and probe were designed and applied in the current study. Results showed high eDNA concentrations in Dasha fishing ground, Yangtze Estuary fishing ground and Zhoushan fishing ground. Higher concentrations of eDNA were found in water depths around 30–40 m. The eDNA hotspots were mainly concentrated at 29°N-33°N,122°E-125°E, but no significant differences in neither horizontal nor vertical distributions were observed. Temperature was a critical factor in the presence and concentration of eDNA amongst environmental variables in the correlation analysis. In addition, a linear formula between environmental factors and the eDNA concentration of black sea bream was predicted, which may be helpful for future fishery resource surveys. To summarise, the present paper provides a new idea for marine resource surveys. It also affords a method and theoretical basis for applying the eDNA technology in fisheries surveys, which is expected to become an essential tool for fisheries resource surveys in the future.